An aid to the MRCP PACES - Banerjee, D. (Wiley-Blackwell, 2013)
"The first volume in this revised suite of the best-selling MRCP PACES revision guides is now fully updated. It reflects both feedback from PACES candidates as to which cases frequently appear in each station. Also taken into account is the new marking system introduced in which the former four-point marking scale has been changed to a three-point scale and candidates are now marked explicitly on between four and seven separate clinical skills"--Provided by publisher.